Vaccination with recombinant Plasmodium vivax MSP-10 formulated in different adjuvants induces strong immunogenicity but no protection (2009)
Although largely considered benign, Plasmodium vivax causes disease in nearly 75 million people each year and the available strategies are not sufficient to reduce the burden of disease, therefore pointing to vaccine development as a cost-effective control measure. In this study, the P. vivax merozoite surface protein 10 (MSP-10) was expressed as a recombinant protein in Escherichia coli and purified by affinity chromatography. High antigenicity was observed since sera from P. vivax-infected patients strongly recognized rPvMSP10. The immunogenicity of rPvMSP10 was tested in Aotus monkeys, comparing responses induced by formulations with Freund's adjuvant, Montanide ISA720 or aluminum hydroxide. All formulations produced high antibody titers recognizing the native protein in late schizonts. Despite inducing strong antibody production, none of the formulations protected immunized Aotus monkeys upon experimental challenge. © 2009 Elsevier Ltd. All rights reserved.